Study the effect of mycorhizal fungi on tomato wilt disease caused by Fusarium oxysporum - Al-Maghribi, Sabah; Taweel , Mohamad; Rizk, Boushra (Latakia University Journal -Biological Sciences Series, 2013)
The effect mycorhizal fungi on tomato wilt disease caused by Fusarium oxysporum was studied. The results showed that % of disease incidence reduced in treatment whit mycorrhizal fungi . % of disease incidence reached to 33% when plants infected with mycorrhizae and Fusarium wilt compared to plants infected with Fusarium wilt just where% of disease incidence reached to 70% .The results showed a sighificant increased in plant height ,leaf number , fresh and dry matter of shoot and root in treated plants with mycorrhiza and Fusarium wilt compared whit treated plants with Fusarium wilt.The increase in plant height reached 24.13% ,16.93% in leaf number,36.13% in wet weight of shoot ,48.14 in wet weight of root,30.37% in dry weight of shoot and 29.18% in dry weight of root in treated plants with mycorrhiza and Fusarium wilt.